Financial constraints of ASEAN firms: Impact alleviation by ESG pillars - Ng, Yee Ling; Lau, Wei Theng; Soh, Wei Ni; Razak, Nazrul Hisyam Ab (The Economics and Finance Letters, 2024)
The purpose of this study is to examine whether ESG plays a positive moderating role in the negative relationship between financial constraint, the Kaplan-Zingales (KZ) and Whited and Wu (WW) indexes, and firm performance: Return of Asset (ROA) and Return of Equity (ROE). This study uses information from the Thomas Refinitiv database, which covers the Association of Southeast Asian Nations (ASEAN-5): Indonesia, Malaysia, Singapore, Thailand, and the Philippines non-financial firms from 2011 to 2019. Fixed-effects (FE) are used as the baseline model, and random-effects (RE) act as the robustness of methods. The results show that the main effect of financial constraints is to act as an obstacle to firm performance. However, the marginal effects of financial constraints can be improved in the presence of ESG. Firms with a high ESG score are better at alleviating the adverse impact of financial constraints as compared to those with a low ESG score. When the ESG score is further broken down into three sub-pillar dimensions, the S-score is of the greatest magnitude in its moderating role in the ESG breakdown. The findings have important implications: effective financial support and the source of funding from the government are crucial to supporting firm performance. ESG-compliant strategies should also be formulated to encourage ESG disclosure, which leads to increased capital allocation efficiency. The firms should be stringent on S-score, which helps drive the company as employees respond by giving their best. Governments and firms need to deploy ESG guidelines in order to succeed in thriving competitive firm performances.